THE IMPROVEMENT OF ORGANIZATIONAL CITIZENSHIP BEHAVIOURS (OCB) THROUGH ISLAMIC WORK ETHIC, AFFECTIVE COMMITMENT, AND THE IDENTITY OF THE ORGANIZATION - Gunadi Wibowo; Wuryanti Wuryanti (IJIBE (International Journal of Islamic Business Ethics), 2017)
Employee who are willing to voluntarily help fellow co-workers to do work outside the assigned job description and the assistance provided is not included in the performance assessment, called organizational citizenship behavior (OCB). Podsakoff et.al (2000) states that OCB can influence organizational effectiveness because it can help improve co-workers productivity, increase managerial productivity and streamline the use of organizational resources for productive purposes. This research was conducted to identify the effect of Islamic work ethics, affective commitment and organizational identity on OCB. The data were collected from 110 employees at the Muhammadiyah Islamic Hospital of Kendal and the Muhammadiyah Darul Istiqomah Hospital of Kendal. The data were later analyzed using Structural Equation Modeling (SEM) using the Analysis of Moment Structure (AMOS 24) software. The result indicate that affective commitment and organizational identity have a significant effect on OCB while Islamic work ethics have no significant effect on OCB. The researcher hopes that this research can be developed in future research by adding other variables related to OCB that may have a greater influence on OCB.Keywords: OCB, Islamic work ethics, affective commitment, organizational identity